EFEKTIFITAS PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI KELAS XI SMA NEGERI 1 ANGKOLA BARAT - Erna Mala Fitri; Rahmatika Elindra; Rabiyatul Adawiyah Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study is to describe the effectiveness of using inquiry learning model on students’ mathematical problem solving ability on the topic of arithmetic line and sequence at the eleventh grade students of SMA Negeri 1 Angkola Barat. The research was conducted by applying experimental method (one group pretest post test design) with 35 students as the sample and they were taken by using random sampling technique from 172 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using inquiry learning model was 3.67 (very good category) and (b) the average of students’ arithmetic line and sequence achievement before using inquiry learning model was 65 (enough category) and after using inquiry learning model was 95 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 16) and N-Gain, the result showed the significant value was less than 0.05 (0.000<0.05) and g=0.86 (high effective). It means, inquiry learning model had high effective on students’ mathematical problem solving ability on the topic of arithmetic line and sequence at the eleventh grade students of SMA Negeri 1 Angkola Barat.